Ethnic conflict regulation and Lithuanian experience in the last decade - Statkus, Nortautas (Politologija, 2000)
There exists a rather generally accepted view that ethnic diversity of a polity is an additional source of internal instability and sometimes negatively affects the state’s international standing. Therefore, states rarely abstain from regulating inter-ethnic relations within the state. States have used in the past and employ in the present various methods of ethnic accommodation ranging from genocide to consociational solutions. An article embraces a brief discussion of strategies and methods employed by the states to resolve ethnic conflicts. As ethnic policy of a state depends on traditions of incorporation of minorities, its international position and characteristics of a “core nation” and minorities (demography, territorial distribution, ethnic division of labour, level of political institutionalisation and mobilisation of ethnicity, nature and distinctiveness of ethnic markers), the article analyses ethnic policies and minorities’ regime in Lithuania in terms of the above-mentioned variables during the past decade. Ethnic minorities are of dual origin in Lithuania: Poles are predominantly indigenous and the majority of the Russian-speaking minority (Russians, Ukrainians, Belorussians) is a product of recent migration. Also, there exist differences of geographical distribution and socio-economic status between major minorities in Lithuania. Therefore, the Lithuanian official policy of integration and cultural autonomy has brought about different results to Poles and Russian-speakers and has delineated distinctive contours for minorities’ future situation. Thus, the article helps to clarify the issue of ethnic minorities’ susceptibility to acculturation/integration, assimilation or some kind of territorial autonomy in Lithuania, and adequacy of the actual state’s ethnic policy in relation to attainment of the declared goals of multiculturalism and ethnic integration. The recommendations for improvement of the Lithuanian ethnic policy are proposed.